FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN SEPEDA MOTOR MERK YAMAHA (STUDY KASUS PADA PT. MURNI JAYA MOTOR CABANG PENEROKAN KABUPATEN BATANGHARI) - Ahmad Tarmizi (Universitas Batanghari Jambi, 2014)
The purpose of the study is diiharapkan in this research is to determine the effect of the decision kosumen consisting of cultural factors, social, personal, and psychological to the purchase of the Yamaha brand motorcycles and to determine factors among cultural, social, personal, and psychological more influence on decision consumers in the purchase of the Yamaha brand motorcycles. Studies using the survey method, does not have to examine all individuals in the population, because it would require huge costs and time. Research can be done by examining a portion of the population (sample), In this study Total population is the number of consumers in the year 2012 as many as 277 population in question here is the consumer at PT. Pure Jaya Motor Branch Penerokan Batang regency sample size in this study was 74 samples. Cultural factors, social, personal and psychological jointly have no effect on purchasing decisions Yamaha brand motorcycles. With the calculated F value is smaller than the F table (1.793 <1.96) then H0 is rejected and H1 is accepted. Cultural factors, social and psychological no partial effect on purchasing decisions Yamaha brand motorcycles. This is indicated by the value of T count is smaller than the T table (0.662 <1.671) and in that case H0 is rejected and H1 is accepted. While personal factors influence purchasing decisions partially on Yamaha brand motorcycles. This is indicated by the value of T is bigger than the T table (2.053> 1.671) it is thus H0 is accepted and H1 is rejected.Key word : Decision, Purchasing, Motor